Optimal Broadcast Strategy-Based Producer Mobility Support Scheme for Named Data Networking - Hussaini, Muktar; Awang Nor, Shahrudin; Ahmad, Amran (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Named Data Networking is a consumer-driven network that supports content consumer mobility due to the nature of in-network catching. The catching suppressed unnecessary Interest packets losses by providing an immediate copy of the data and consumer-driven nature influencedthe mobile consumer to resend unsatisfied Interest packet immediately after the handoff. Once the producer moves to a new location, the name prefix changed automatically after handoff to the new router or point of attachment. The entire network lacks the knowledge of producer movement unless if the producer announces its new prefix to update the FIBs of intermediate routers. Lack of producer’s movement knowledge causes an increase of handoff latency, signaling overhead cost, Interests packets losses, poor utilization of bandwidth and packets delivery. Therefore, there is needs to provide substantial producer mobility support to minimize the handoff latency, handoff signaling overhead cost, reduce the unnecessary Interest packets loss to improve data packets delivery once a content producer relocated. In this paper, broadcasting strategy is introduced to facilitate the handoff procedures and update the intermediate routers about the producer movement. Hence, analytical investigation result of this paper addresses the deficiency of Kite scheme by minimizing handoff signaling cost and provides data path optimization after the handoff.